C-arm Positioning Is a Significant Source of Radiation in Spine Surgery. Issue 9 (1st May 2017) - Reiser, Elizabeth W.; Desai, Rupen; Byrd, Sarah A.; Farber, Harrison; Chi, Deborah; Idler, Cary S.; Isaacs, Robert E.
Abstract : Study Design: Prospective chart review. Objective: It is well-known that radiation exposure during minimally invasive spine procedures can be substantial. Less interest has focused on setup radiation exposure before incision, including preoperative images used for surgical approach. The present study seeks to better quantify the significance of setup radiation in the total radiation exposure of minimally invasive spine surgery. Summary of Background Data: Radiographic localization is necessary in minimally invasive spine procedures to visualize anatomy, but increased radiation exposure is associated with health risks. Preoperative imaging for anatomical localization has not been previously analyzed as an appreciable source of radiation. Methods: From an institutional review board–approved database of more than 1100 procedures, the minimally invasive spine cases with recorded set-up radiation were extracted. The total radiation, set-up radiation, and procedure type data were evaluated. Statistics were generated using a chi-squared analysis. Results: Set-up and total radiation data were collected for 270 spine surgeries performed by four surgeons at two locations. There were 30 thoracic and 240 thoracolumbar/lumbar cases; 78 anterior and 192 posterior cases. Average total radiation (set-up and intraoperative) was 8.04 rad, and average setup radiation was 1.90 rad (28%, std 2.97 rad) across all cases. On average for the thoracolumbar/lumbar cases, set-up radiation accounted for almost 25% of total radiation with 1.76 rad from setup out of 8.16 rad total. Thoracic-only cases often necessitated even more images for localization, generating an average set-up/total percentage of 52%. Across all procedures, set-up radiation significantly increased the total radiation exposure because it accounted for more than 25% of the total procedure. Conclusion: Radiation exposure during preoperative localization can be substantial. Operating room personnel should recognize the high percentage of radiation that occurs during set-up, and merit should be given to techniques and technologies that can limit unnecessary radiation exposure during this portion of the procedure. Level of Evidence: 2